La pedagogia come sapere oggi: statuto epistemico e paradigma educativo - Franco Cambi (Firenze University Press, 2017)
Pedagogy should rethink about itself, steadily, in its being science. Pedagogy is a complex science, as John Dewey suggests, but i salso a science with a strong crit-ical consciousness that is active in all its think/act. It is also a critical pedagogy that has not only an epistemological role, but also has a innovative and utopical function.